Optimization schemes for wireless sensor network localization - Niewiadomska-Szynkiewicz, Ewa; Marks, Michał (Zielona Góra: Uniwersytet Zielonogórski)
Many applications of wireless sensor networks (WSN) require information about the geographical location of each sensor node. Self-organization and localization capabilities are one of the most important requirements in sensor networks. This paper provides an overview of centralized distance-based algorithms for estimating the positions of nodes in a sensor network. We discuss and compare three approaches: semidefinite programming, simulated annealing and two-phase stochastic optimization - a hybrid scheme that we have proposed.
Keywords: wireless sensor networks; localization; stochastic optimization; simulated annealing